Leadership and Organizational Culture Analysis on Organizational Citizenship Behavior (OCB) at PT. Hatten Bali - Ariyanti, Ni Kadek Irma; Santra, I Ketut; Lasmini, Ni Ketut (Jurnal Riset Bisnis dan Investasi, 2017)
This study aimed to analyze the influence of leadership and organizational culture on Organizational Citizenship Behavior employees. The study is a quantitative research. The data used in this study was collected through questionnaires and implemented to 106 of permanent employees in PT. Hatten Bali. The results of this study indicates that: 1) leadership have positive and significant effect on organizational citizenship behavior which indicated by coefficient regression value 0,297 and significant value 0,003, 2) organizational culture have positive and significant effect on organizational citizenship behavior which indicated by coefficient regression value 0,144 and significant value 0,039, and 3) leadership and organizational culture have simultaneously effect on organizational citizenship behavior which indicated by f-count value 6,846 > f-table and significant value 0,002. Regression analyze result adjusted R2 value 0,117. This indicates that organizational citizenship behavior can explained by leadership and organizational culture variable of 11,7 % while the remaining 88,3% explained by the others variable outside of this study.